Synthesis of water soluble cyclotriphosphazenes with thiazole-containing side groups: Amphiphilic and hydrolytic degradable - Uslu, Aylin; Ozcan, Elif (Pergamon-Elsevier Science Ltd, 2018)
A series of a new class of amphiphilic cyclophosphazene derivatives, consisting of thiazole side groups and polyethyleneglycol or ethyleneglycol moieties as cosubstituent groups were prepared and characterized using spectroscopic methods. Reported compounds were examined in order to investigate their hydrolytic degradation and concentration-dependent lower critical solution temperatures (LCST) behaviors in aqueous solution. These amphiphiles bearing polyethyleneglycol as a hydrophilic group were found to have LCST being close body temperature compared with ethyleneglycol analogues and potentially useful for biomedical applications. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cyclophosphazene; Thiazole; LCST; Hydrolytic degradation; P-31 NMR